CRISPR/Cas: from adaptive immune system in prokaryotes to therapeutic weapon against immune-related diseases: CRISPR/Cas9 offers a simple and inexpensive method for disease modeling, genetic screening, and potentially for disease therapy. (2nd January 2020) - Garcia-Robledo, Juan Esteban; Barrera, María Claudia; Tobón, Gabriel J.
Abstract: CRISPR/Cas evolved as an adaptive immune system in bacteria and archaea to inactivate foreign viral and plasmid DNA. However, the capacities of various CRISPR/Cas systems for precise genome editing based on sequence homology also allow their use as tools for genomic and epigenomic modification in eukaryotes. Indeed, these genetic characteristics have proven useful for disease modeling and testing the specific functions of target genes under pathological conditions. Moreover, recent studies provide compelling evidence that CRISPR/Cas systems could be useful therapeutic tools against human diseases, including cancer, monogenic disorders, and autoimmune disorders. Highlights: CRISPR/Cas evolved as an adaptive immune system in bacteria and archaea. CRISPR/Cas systems are nowadays used as tools for genomic modification. CRISPR/Cas systems could be useful therapeutic tools against human disease, including autoimmune conditions.